Rekonstruksi Unsur Penganiayaan yang Mengakibatkan Kematian oleh Aparat: Studi Kasus Siswa MTs dalam Perspektif Doktrin Dolus dan Culpa (Pusat Riset dan Inovasi Nasional, 2026)
The death of a Madrasah Tsanawiyah (MTs) student allegedly linked to police action raises significant legal issues concerning the limits of the use of force and the construction of criminal liability. This study aims to reformulate the elements of assault resulting in death by integrating the objective element (actus reus) and the subjective element (mens rea) within the framework of the doctrines of dolus and culpa. It also seeks to develop a model of criminal liability analysis that is more transparent, accountable, and oriented toward the protection of a child’s right to life. This research employs a normative juridical method using statutory, conceptual, and case approaches, supported by a literature review of legislation, court decisions, and criminal law scholarship. Data are analyzed qualitatively through grammatical, systematic, and teleological interpretation. The findings indicate that proving the act and the resulting death alone is insufficient without clearly establishing the form of fault. The distinction between dolus eventualis and culpa lata constitutes a decisive factor in determining the classification of the offense and the degree of criminal liability. Ambiguity in identifying the spectrum of fault may lead to sentencing disparities and weaken the principle of geen straf zonder schuld (no punishment without fault). Therefore, this study proposes a reconstruction of the elements of the offense that places proof of mens rea at the center of assessing police accountability while ensuring the protection of the child’s right to life.